Pretreatment central quality control for craniospinal irradiation in non-metastatic medulloblastoma - Dietzsch, Stefan; Braesigk, Annett; Seidel, Clemens; Remmele, Julia; Kitzing, Ralf; Schlender, Tina; Mynarek, Martin; Geismar, Dirk; Jablonska, Karolina; Schwarz, Rudolf; Pazos, Montserrat; Walser, Marc; et al. (Strahlentherapie und Onkologie, 2021)
Several studies have demonstrated the negative impact of radiotherapy protocol deviations on tumor control in medulloblastoma. In the SIOP PNET5 MB trial, a pretreatment radiotherapy quality control (RT-QC) program was introduced. A first analysis for patients enrolled in Germany, Switzerland and Austria with focus on types of deviations in the initial plan proposals and review criteria for modern radiation technologies was performed.